1998
DOI: 10.1016/s1097-2765(00)80160-4
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Allosterically trans-Activated Ribozyme, the Maxizyme, with Exceptional Specificity In Vitro and In Vivo

Abstract: We have constructed an allosterically controllable novel enzyme (designated maxizyme) that can be transcribed in vivo under the control of a human tRNA(Val) promoter. The maxizyme has sensor arms that can recognize target sequences, and in the presence of such a target sequence only, it can form a cavity that can capture catalytically indispensable Mg2+ ions. As a target for a demonstration of the potential utility of the maxizyme, we chose BCR-ABL mRNA, the translated products of which cause chronic myelogeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
166
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(174 citation statements)
references
References 36 publications
6
166
2
Order By: Relevance
“…13 As the M-BCR/ABL mRNA is an attractive target for Leukemia treatment [14][15][16] attempts at suppression of expression of this M-BCR/ABL oncogene, has been done mainly at the mRNA level. Most successful of these approaches has been the use of so called maxizymes which have been shown to effectively cleave chimeric M-BCR/ABL RNA in vitro and in vivo 17 , cause apoptosis in cultured leukemic cells with the Philadelphia chromosome 18,19 and to suppress progression of Leukemia in mice 20 . It also has been demonstrated that exogenously delivered chemically synthesized dsRNA (siRNA) directed at the M-BCR/ABL fusion site, is effective in killing leukemic cells.…”
Section: Introductionmentioning
confidence: 99%
“…13 As the M-BCR/ABL mRNA is an attractive target for Leukemia treatment [14][15][16] attempts at suppression of expression of this M-BCR/ABL oncogene, has been done mainly at the mRNA level. Most successful of these approaches has been the use of so called maxizymes which have been shown to effectively cleave chimeric M-BCR/ABL RNA in vitro and in vivo 17 , cause apoptosis in cultured leukemic cells with the Philadelphia chromosome 18,19 and to suppress progression of Leukemia in mice 20 . It also has been demonstrated that exogenously delivered chemically synthesized dsRNA (siRNA) directed at the M-BCR/ABL fusion site, is effective in killing leukemic cells.…”
Section: Introductionmentioning
confidence: 99%
“…1 Various gene transduction systems have been developed, the most widely investigated of which is the murine leukemia virus (MLV) vector system, but human blood cell transduction efficiency has been uniformly low. [2][3][4][5] We have demonstrated previously that a novel allosterically controllable ribozyme, designated the Maxizyme, induces cell death in a chronic myelogenous leukemia (CML) cell line harboring the b2a2 type bcr-abl oncogene in vitro 6 and in vivo, 7 but we could not efficiently transduce Maxizyme into primary cells of leukemia patients. The lack of efficient gene transduction techniques has so far hampered efforts to provide gene therapy for hematological disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Although no allosterically regulated ribozymes have yet been identified in nature (but see the section below on oligonucleotide-regulated ribozymes), many have been developed artificially. This has been accomplished by the often complementary approaches of rational design (Tang andBreaker 1997, 1998;Kuwabara et al 1998;Vaish et al 2002;Wang and Sen 2002) and in vitro selection (Koizumi et al 1999;Robertson and Ellington 1999;Soukup and Breaker 1999b). Allosteric regulation has been imposed onto the hammerhead (Kertsburg and Soukup 2002), HDV (Kertsburg and Soukup 2002), hairpin , Tetrahymena group I intron (Kertsburg and Soukup 2002), and X-motif ribozymes (Kertsburg and Soukup 2002).…”
Section: Allosteric Ribozyme Sensors (Aptazymes) and General "Communimentioning
confidence: 99%